Lecturers' Pedagogic Competence Profile of Politeknik Penerbangan Palembang - Komalasari, Yeti; Kristiawan, Muhammad; Danim, Sudarwan; Badeni, Badeni (Graduate Program Magister Manajemen Pendidikan, 2023)
This study was conducted to determine the pedagogic competency profile of Politeknik Penerbangan Palembang lecturers in the Diploma IV Study Program in Airport Engineering Technology (TRBU), Diploma III Airport Management Study Program (MBU) and Diploma III Aviation Rescue and Fire Fighting Study Program (PPKP). The type of research used in this research is descriptive quantitative. The research subjects were all lecturers from each study program, both PSDT lecturers and practitioner/industry lecturers. The data used is data collected through observation, questionnaires and documentation studies. Data analysis uses the average and percentage scores. This study aims to look at the pedagogic abilities of lecturers who are assessed through 5 (five) assessment indicators. The results of this study indicate the ability of pedagogic competence on indicators of understanding students in depth (23.18%) designing learning including understanding the educational foundation for the benefit of learning (20.01%) carrying out learning (21.46%) designing and implementing learning evaluations (20.012%) developing competence students to actualize their various competencies (20.012%) overall the lecturer's pedagogical competence (47.28%) is in the good category. Indicators of success can be seen in the results of the pedagogic competence of Politeknik Penerbangan Palembang lecturers who currently have good pedagogic competence. These results have implications for giving awareness to lecturers of the importance of mastering pedagogic competencies as an effort to improve the quality and quality of the education system at the Politeknik Penerbangan Palembang.